Key role of the sympathetic microenvironment for the interplay of tumour necrosis factor and interleukin 6 in normal but not in inflamed mouse colon mucosa. Issue 8 (21st April 2005) - Straub, R H; Stebner, K; Härle, P; Kees, F; Falk, W; Schölmerich, J
Abstract : Background: In the intestinal tract, the role of sympathetic neurotransmitters has been largely ignored in mucosal neuroimmunology. Aim: Our aim was to investigate the influence of the sympathetic microenvironment on the mucosal interplay of tumour necrosis factor (TNF) and interleukin 6 (IL-6). Methods: Colon strips of normal and colitic BALB/c mice were superfused in vitro. Tissue was electrically stimulated to investigate the influence of endogenous norepinephrine (NE) on secretion of IL-6, with or without anti-TNF antibodies (anti-TNF) and adrenoceptor antagonists. IL-6 was secreted from macrophages. Results: Superfusion with anti-TNF stimulated IL-6 secretion in normal but not in colitic colon (p<0.005). Parallel superfusion with a β-adrenergic antagonist abrogated this phenomenon. Anti-TNF increased release of NE from normal colonic strips (p<0.05), which demonstrates TNF induced inhibition of preterminal NE release. In colitic mice, anti-TNF did not change NE release. In the presence of anti-TNF, exogenous and endogenous NE stimulated colonic IL-6 secretion via β-adrenoceptors in normal (p<0.001) but not in colitic mice. In the absence of anti-TNF, endogenous and exogenous NE inhibited IL-6 secretion via the β-adrenoceptor in normal but not in colitic mice (p<0.01). Colitic mice demonstrated loss of sympathetic nerve fibres. Conclusions: Modulation of mucosal IL-6 is largely dependent on the sympathetic microenvironment and availability of local TNF in normal but not in colitic mice. Anti-TNF strategies may lead to an increase in the proinflammatory cytokine depending on adrenergic tone. This would be relevant with normal sympathetic innervation, which is lost in colitic mice. We present a model of sympathetic regulation of colonic macrophage TNF and IL-6 secretion.